African female managers in harbors. Struggles and contradictions in the intersection of gender, age, and religion - (:unkn) unknown (My University, 2016)
Our paper investigates African female managers working in harbors. We discovered the complexities of contextual factors and the intersection of gender, race, age, and religion. Women – in our research – are privileged in their countries, most of them are living in wealthy and powerful families, which have strong connection with the West. While being female managers they often experience even overt discrimination due to their gender in their workplace. At the same time some of them perceiving their working life as constant struggles, others argues that gender inequality is not an issue in their organizations and their countries.
Keywords: African Research